2016
DOI: 10.1186/s40001-016-0204-2
|View full text |Cite
|
Sign up to set email alerts
|

An update on the clinical diagnostic value of β-hCG and αFP for intracranial germ cell tumors

Abstract: BackgroundPathological examination combined with tumor markers has become a standard for the diagnosis of intracranial germ cell tumors (ICGCTs), but the current concept of ‘secreting germ cell tumors’ and three empirically highly specific diagnostic criteria (β-hCG ≥ 50 IU/L or αFP ≥ 10 ng/mL; β-hCG ≥ 100 IU/L or αFP ≥ 50 ng/mL; β-hCG > 50 IU/L or αFP > 25 ng/mL) are not based upon pathology examination or CSF cytology. Further investigation is needed to re-evaluate their value.MethodsA multidisciplinary diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 26 publications
(32 reference statements)
1
23
1
Order By: Relevance
“…CSF cytology together with magnetic resonance imaging study, are extremely important for the diagnosis of the potential leptomeningeal infiltration. CSF dispersal stages are categorised as M0 (no tumour cells found in CSF), M1 (varied numbers of neoplastic cells found in CSF), M2 (involvement of ventricles and subarachnoid region), M3 (involvement of the spinal cord) and M4 (extracranial metastases) . Our case was an M2 case.…”
Section: Discussionmentioning
confidence: 96%
“…CSF cytology together with magnetic resonance imaging study, are extremely important for the diagnosis of the potential leptomeningeal infiltration. CSF dispersal stages are categorised as M0 (no tumour cells found in CSF), M1 (varied numbers of neoplastic cells found in CSF), M2 (involvement of ventricles and subarachnoid region), M3 (involvement of the spinal cord) and M4 (extracranial metastases) . Our case was an M2 case.…”
Section: Discussionmentioning
confidence: 96%
“…Elevated serum levels occur in other malignancies, tumor lysis syndrome, primary hypogonadism and precocious puberty. Elevated CSF levels occur in pituitary adenomas, craniopharyngiomas, arachnoidal cysts and Langerhans cell histiocytosis ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…The decision limits were recently reassessed in a study comparing hCG and AFP values in 58 GCTs confirmed by pathology. This study concluded that serum and CSF should have different decision limits, and lower decision limits of ≥8.2 IU/L for hCG and ≥3.8 μg/L AFP in CSF were proposed (7).…”
Section: Articlesmentioning
confidence: 96%
“…This result subsequently helps direct appropriate treatment (2)(3)(4) and reduces the risk of surgery-related complications in this subset of patients (5). Increased concentrations of AFP in CSF support the diagnosis of yolk sac tumors/yolk sac components of mixed GCTs, whereas high concentrations of hCG in CSF support the diagnosis of choriocarcinomas/ choriocarcinomatous components of mixed GCTs (6,7).…”
mentioning
confidence: 93%
See 1 more Smart Citation